Improving students’ mathematical logical intelligence through the online-based integration of local wisdom of Sulapa Eppa Walasuji - F.A, A. Nurannisa; Asfar, Andi Muhammad Irfan Taufan; Asfar, Andi Muhamad Iqbal Akbar; Syaifullah, Adji (Al-Jabar: Jurnal Pendidikan Matematika, 2021)
Mathematical logical intelligence is one of the skills that are needed in the 21st century related to mathematical problem-solving skills. The importance of this skill is not in line with the facts on the ground, where students are still weak in counting and using logic in problem solving. The purpose of this research is to improve students’ mathematical logical intelligence through the online-based integration of local wisdom of Sulapa Eppa Walasuji. Sulapa Eppa Walasuji is one of the Bugis-Makassar local wisdoms with a unique pattern, appropriate to be used as a medium for learning transformation of geometry. Through the integration of local wisdom, Sulapa Eppa Walasuji can create contextual mathematics learning, so that students can easily understand the material by connecting real-life concepts. This research includes experimental research with a quasi-experimental design of the nonequivalent control group design type. The research instrument used was a mathematical logical intelligence test consisting of five essay questions. The data analysis used is descriptive statistics with gain score and effect size testing. The results showed that the mathematical logical intelligence of experimental class students increased by 43.16 with the effective contribution of the r effect size being 0.910. This indicates that the online-based integration of Sulapa Eppa Walasuji can improve students’ mathematical logical intelligence.